New excavations in Northwestern Greece: The Neolithic settlement of Avgi, Kastoria - Stratouli, G.; Bekiaris, T.; Katsikaridis, N.; Kloukinas, D.; Koromila, G.; Kyrillidou, S. (Journal of Greek Archaeology, 2020)
Neolithic Avgi is one of several Neolithic sites that have been recently investigated in northern Greece. During the last decades, there has been an outburst of excavations in Western and Central Macedonia, Greece that are changing our knowledge of the Neolithic period, to the point that it has no precedent in the history of research for any other region of Greece. These are intensive, large-scale excavations, with meticulous documentation of the stratigraphic information, and systematic collection of findings of all sorts.2 Many follow internationallystandardised sampling protocols and have a highly interdisciplinary rationale, with an emphasis on the collection of bioarchaeological, geoarchaeological, and micro-environmental proxies. The first visible result is high-quality excavation research, only a fragment of which is unfolded here.